21+3f=9-3f

Simple and best practice solution for 21+3f=9-3f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21+3f=9-3f equation:


Simplifying
21 + 3f = 9 + -3f

Solving
21 + 3f = 9 + -3f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '3f' to each side of the equation.
21 + 3f + 3f = 9 + -3f + 3f

Combine like terms: 3f + 3f = 6f
21 + 6f = 9 + -3f + 3f

Combine like terms: -3f + 3f = 0
21 + 6f = 9 + 0
21 + 6f = 9

Add '-21' to each side of the equation.
21 + -21 + 6f = 9 + -21

Combine like terms: 21 + -21 = 0
0 + 6f = 9 + -21
6f = 9 + -21

Combine like terms: 9 + -21 = -12
6f = -12

Divide each side by '6'.
f = -2

Simplifying
f = -2

See similar equations:

| (x/6)-2=(x/6) | | (2x+1)(-6x+5)=0 | | 0.002h-4=0.02+4h-8 | | 3x+7/4=-2 | | 2377960+26x=-1825 | | 15x+1=yforc | | 3+(x-3)=x+1 | | 12y=11(y+12) | | 4h-8=3n+2 | | 4x+(3/4)=5x-(3/4) | | 14(9x-9)-7x=-9 | | 28-6(2x+5)=124 | | (2(x+2)/3)=5x-3 | | 4.8y=-3.36 | | -10n+12=-6n-4 | | 0.08+0.01(x+2)=-0.02(3-x) | | 2-y=12 | | -3=-(x+7) | | 7v^2-42=-35k | | -10=-2+12d | | -5=x/19-4 | | (2/15)x-(1/5)=1 | | 1-25q/4=-3q/4-1/2(5q+2) | | 20xz-35yz+4x-7y= | | -1=x-5/6 | | 19+h/-3=8 | | X-(-10)=21 | | 4x-7/5=x-5 | | 7y=14/3 | | 3/2x-6=0 | | (2/7)x+(4/7)=(-4/7) | | 7x-3(3+4x)=19 |

Equations solver categories